Small pumps and poor farmers in Sub-Saharan Africa: an assessment of current extent of use and poverty outreach - Namara, R. E.; Gebregziabher, Gebrehaweria; Giordano, M.; Fraiture, Charlotte de (2023)
The expansion of irrigation in Sub-Saharan Africa has been slow. In Asia, the rapid expansion of smallholder irrigation systems was attributed in part to the availability and affordability of motorized pumps. This paper appraises the current extent of pump-based irrigation in Sub-Saharan Africa; profiles the socio-economic and demographic attributes of current pump adopters; and assesses the poverty outreach of small-pump technology. It shows that private smallholder irrigation is practised mainly by the wealthier farmers. The development of groundwater irrigation requires targeted and deliberate public-policy interventions and institutional support focusing on the more marginal farmers.